The Role of Virtual Marketing in Transforming Modern Agribusiness: Opportunities, Challenges, and Strategic Implications - Dr Sajimon P.P.; V Basil Hans (Journal of Advanced Research in Economics and Business Management, 2026)
Digital technologies have changed the way agribusinesses work in a big way, especially when it comes to marketing. Virtual marketing has become a strategic tool that helps agribusiness companies access more customers, get more involved with them, and make their supply chains work better. This article talks about how virtual marketing is used in modern agriculture and how it affects market access, brand awareness, cost savings, and competition. Agribusiness companies can get around the limitations of geography and infrastructure by using digital platforms like social media, e-commerce sites, mobile apps, and data-driven marketing tools. Agribusiness is very important for the growth of the global economy, food security, and job creation, especially in developing and rising economies. Agribusiness marketing has historically depended on physical markets, intermediaries, and direct transactions, which frequently restrict market access, price transparency, and producer profitability. The rapid evolution of information and communication technologies (ICTs) has begun to reshape the agribusiness landscape, creating new opportunities for efficiency, innovation, and competitiveness. The study also discusses key challenges associated with virtual marketing adoption, including limited digital literacy, inadequate infrastructure, cybersecurity concerns, and regulatory issues, particularly in developing economies. The paper says that adding virtual marketing methods to agricultural models is necessary for long-term growth, higher profits, and the flexibility to adapt to a global market that is becoming more digital.